2019
DOI: 10.1103/physrevlett.123.243903
|View full text |Cite
|
Sign up to set email alerts
|

Attosecond Pulse Amplification in a Plasma-Based X-Ray Laser Dressed by an Infrared Laser Field

Abstract: We suggest a technique to amplify a train of attosecond pulses, produced by high-harmonic generation (HHG) of an infrared (IR) laser field, in an active medium of a plasma-based X-ray laser. This technique is based on modulation of transition frequency of the X-ray laser by the same IR field, as used to generate the harmonics, via linear Stark effect, which results in redistribution of the resonant gain and simultaneous amplification of a wide set of harmonics in the incident field. We propose an experimental … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 54 publications
1
32
0
Order By: Relevance
“…Both possibilities are provided by coherent dressing of the neon-like active medium of an X-ray laser with an intense infrared (IR) laser field. It is closely related to our recent work [27], which has shown the possibility to amplify a set of linearly polarized HHs in a hydrogenlike active medium of a plasma-based X-ray laser dressed by a replica of a fundamental-frequency IR field with the same linear polarization. However, in the hydrogenlike medium the amplification of elliptically or circularly polarized HHs is prohibited, since the redistribution of the gain to the frequencies of harmonics is caused by the IR-field-induced sub-laser-cycle linear Stark effect and occurs only for XUV/X-rays with the same linear polarization as that of the modulating field, whereas for radiation with orthogonal polarization the gain remains localized at the single resonance frequency.…”
Section: Introductionsupporting
confidence: 63%
“…Both possibilities are provided by coherent dressing of the neon-like active medium of an X-ray laser with an intense infrared (IR) laser field. It is closely related to our recent work [27], which has shown the possibility to amplify a set of linearly polarized HHs in a hydrogenlike active medium of a plasma-based X-ray laser dressed by a replica of a fundamental-frequency IR field with the same linear polarization. However, in the hydrogenlike medium the amplification of elliptically or circularly polarized HHs is prohibited, since the redistribution of the gain to the frequencies of harmonics is caused by the IR-field-induced sub-laser-cycle linear Stark effect and occurs only for XUV/X-rays with the same linear polarization as that of the modulating field, whereas for radiation with orthogonal polarization the gain remains localized at the single resonance frequency.…”
Section: Introductionsupporting
confidence: 63%
“…It is worth noting that the considered technique of the atomic transition frequency modulation is rather general. In particular, as shown in our recent works [17][18][19] , it can be used also for generation of the attosecond extreme ultraviolet and x-ray pulses or amplification of the attosecond pulses produced via HHG in the active medium of a plasma-based x-ray laser modulated by a strong infrared laser field.…”
Section: Discussionmentioning
confidence: 97%
“…In recent work [19], we proposed a method for amplifying a train of attosecond pulses formed by a set of high-order harmonics of the infrared (IR) field in a hydrogen-like active Photonics 2022, 9, 51 2 of 21 medium of a plasma-based X-ray laser, which is simultaneously irradiated with a replica of the fundamental-frequency IR field used to generate the high harmonics. Due to the linear Stark effect, the positions of the excited-state energy levels of the resonant ions of the active medium follow the local value of the electric field of the laser wave in time and space.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, if the harmonics of different orders at the entrance to the medium are comparable in amplitude, are in-phase, and form a sequence of attosecond pulses, then in the process of amplification, the spectral-temporal properties of radiation (such as the relative amplitudes and phases of harmonics and, as a consequence, the shape and duration of the pulses) are preserved. In [19], it was shown that it is possible to amplify attosecond pulses formed by a set of high harmonics in the "water window" range (2.3-4.4 nm) by one to two orders of magnitude in intensity in the active medium of hydrogen-like C 5+ ions.…”
Section: Introductionmentioning
confidence: 99%